Internalisasi Pendidikan Karakter di Pondok Pesantren - Atika Xena (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
The purpose of this study is to examine how the Internalization of Character Education in the pondok. This research was conducted at the Pondok Pesantren Darul A’mal. This study uses a type of case study research, which is then analyzed by researchers using social construction theory from Peter L Beger & Thomas Luckmann. Then, the researcher used purposive sampling technique. Based on the results of research, it can be concluded that: externalization process, where learning is done by the method of dialogue; objectivities process is to give direct practice to the students; and internalization process where the santri will imitate the person who is considered good and becomes a role model in behaving in pondok. Research on the process of internalizing character education in pondok pesantren is expected to provide understanding for the community that character education can be provided through non-formal education, namely Pondok Pesantren.